Value of N1 Lymph Node Examination in the Prognosis of Patients With pT1-3N0M0 Non-Small Cell Lung Cancer - Wang, Gaoxiang; Wu, Xianning; Sun, Xiaohui; Li, Tian; Xu, Meiqing; Xu, Liangdong; Xie, Mingran (Frontiers in Oncology, 2020)
Objective: This study aimed to analyze the relationship between the number of examined lymph nodes（ELNs） at the N1 station and the postoperative clinicopathological features and prognosis of patients with pT1-3N0M0 non-small cell lung cancer (NSCLC). Methods: The cut-off value of the number of ELNs at the N1 station was obtained using X-tile software analysis. Kaplan-Meier survival curve analysis and the Cox proportional hazard model were used to study the impact of the number of ELNs at the N1 station on the prognosis of postoperative patients with pT1-3N0M0 NSCLC. Results: The median survival time and 1-, 3- and 5-year survival rates of 0 ELNs at the N1 station were 28.0 months and 74.8%, 45.4%, and 21.2%, respectively. The median survival time and 1-, 3-, and 5-year survival rates of 1-4 ELNs at the N1 station were 45.0 months and 85.5%, 55.4%, and 39.1%, respectively. In the group with ≥ 5 ELNs at the N1 station, the median survival time and the 1-, 3- and 5-year survival rates were 59.0 months and 94.0%, 62.7%, and 48.2%, respectively. Both univariate and multivariate Cox regression analyses showed that the number of ELNs at the N1 station, T stage and operation type were independent factors affecting the prognosis of patients with pT1-3N0M0 NSCLC. Conclusion: Increasing the number of ELNs at the N1 station is positively correlated with the long-term survival rate of patients with T1-3N0M0 NSCLC. At least 5 LNs at the N1 station should be examined in pathological examination.